Time for change is now: Experiences of participants in a community-based approach for iron and folic acid supplementation in a rural county in Kenya, a qualitative study. - Mary Wanjira Kamau (PLoS ONE)
Background Iron and Folic Acid Supplementation (IFAS) is recommended by World Health Organization as part of antenatal care to prevent anaemia in pregnancy. In 2010, Kenya adopted this recommendation and the current policy is to provide one combined IFAS tablet for daily use throughout pregnancy, free of charge, in all public health facilities. However, adherence remains low over the years though anaemia in pregnancy remains high. Integration of IFAS into community-based interventions has been recommended because of its excellent outcome. Using Community Health Volunteers (CHVs) to distribute IFAS has not been implemented in Kenya before. Methods Following an intervention study implementing a community-based approach for IFAS in five public health facilities in Lari Sub-County, 19 interviews were conducted among CHVs, nurses and pregnant women participating to describe their experiences. Thematic analysis of data was done using NVivo and findings described, with use of quotes. Findings The nurses, CHVs and pregnant women were all positive and supportive of community-based approach for IFAS. They reported increased access and utilization of both IFAS and antenatal services leading to perceived reduction in anaemia and better pregnancy outcomes. Counselling provided by CHVs improved IFAS knowledge among pregnant women and consequent adherence. The increased IFAS utilization led to main challenge experienced being IFAS stock-outs. All participants recommended complementing antenatal IFAS distribution approach with community-based approach for IFAS. Conclusion Using CHVs to implement a community-based approach for IFAS was successful and increased supplement awareness and utilization. However, the role of CHVs in IFAS programme implementation is not clearly defined in current policy and their potential in IFAS education and distribution is not fully utilized. All participants endorsed integration of community-based approach for IFAS into the antenatal approach to enhance IFAS coverage and adherence among pregnant women for better pregnancy outcomes.